Liberal Arts vs. Applied Programming: The Evolution of University Programs in Manitoba - Smith, Dan (Canadian Journal of Higher Education, 2005)
This investigation seeks to develop data to help understand the direction being taken in university programming in Manitoba over a 35-year period in terms of the perception of alleged growth of the labour market orientation of universities. The impact of the political party in power is examined, as are features of the post-secondary program approval process developed by the intermediary agencies responsible for university matters in Manitoba. Findings suggest that new liberal arts, applied, and mixed programs have increased at roughly the same proportions over the 35-year period in question. Evidence is found, however, of a more recent emphasis on applied programming, supporting claims that university programming is increasingly becoming labour market oriented.